Versions of antihumanism : Milton and others - Fish, Stanley Eugene (New York : Cambridge University Press, 2012)
"Stanley Fish, one of the foremost critics of literature working today, has spent much of his career writing and thinking about Milton. This book brings together his finest published work with brand new material on Milton and on other authors and topics in early modern literature. In his analyses of Renaissance texts, he meditates on the interpretive problems that confront readers and offers a sustained critique of historicist methods of interpretation. Intention, he argues, is key to understanding which pieces of historical data are relevant to literary criticism. Lucid, provocative, direct and inimitable, this new book from Stanley Fish is required reading for anyone teaching or studying Milton and early modern literary studies"--Provided by publisher.
Includes bibliography and index.
Keywords: Milton, John, -- 1608-1674 -- Criticism and interpretation; English literature -- Early modern, 1500-1700 -- History and criticism